2022
DOI: 10.1038/s41598-022-13011-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (E)-2-(1H-tetrazole-5-yl)-3-phenylacrylenenitrile derivatives catalyzed by new ZnO nanoparticles embedded in a thermally stable magnetic periodic mesoporous organosilica under green conditions

Abstract: ZnO nanoparticles embedded in a magnetic isocyanurate-based periodic mesoporous organosilica (Fe3O4@PMO–ICS–ZnO) were prepared through a modified environmentally-benign procedure for the first time and properly characterized by appropriate spectroscopic and analytical methods or techniques used for mesoporous materials. The new thermally stable Fe3O4@PMO–ICS–ZnO nanomaterial with proper active sites and surface area as well as uniform particle size was investigated for the synthesis of medicinally important te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 121 publications
(75 reference statements)
0
18
0
Order By: Relevance
“…The results of using different conditions in model reaction presented in entries (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) Although the reaction time with 15 or 20 mg of the catalyst is slightly less than the reaction time with 10 mg of catalyst, no noticeable change in e ciency was seen. For this reason, the optimal amount of catalyst was chosen to be 10 mg. By using the introduced catalyst components separately in the model reaction, it can be concluded that the prepared nano-catalyst shows better results in proceeding the three-component synthesis of imidazole derivatives.…”
Section: The Morphological Features and Particle Size Of The New Magn...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of using different conditions in model reaction presented in entries (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) Although the reaction time with 15 or 20 mg of the catalyst is slightly less than the reaction time with 10 mg of catalyst, no noticeable change in e ciency was seen. For this reason, the optimal amount of catalyst was chosen to be 10 mg. By using the introduced catalyst components separately in the model reaction, it can be concluded that the prepared nano-catalyst shows better results in proceeding the three-component synthesis of imidazole derivatives.…”
Section: The Morphological Features and Particle Size Of The New Magn...mentioning
confidence: 99%
“…The designed-procedures for the preparation of nanomaterials including magnetic nanoparticles and their catalytic activities are entirely veri ed in the eld of greener and atom-economic reactions especially multicomponent reactions [4][5][6][7] . On the other hand, the use of magnetic decorated organic species is gaining signi cant attention in the eld of catalysis for organic transformations, mainly due to opportunities in providing new structural changes [8][9][10][11][12] . The design and construction of new structures is achieved with the aim of improving the structural characteristics and enhancing the catalytic properties in the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Tetrazole derivatives are most commonly synthesized by [3 + 2] cycloaddition reaction of the corresponding azide and nitrile moieties 105 112 . Therefore, attempts for the production of tetrazole derivatives through new methods have led to the use of 2-benzylidenemalononitrile and sodium azide along these lines 113 , 114 . In continuation of interest to develop new PMOs or their assemblies and exploring their catalytic activities 21 , 22 , 30 , 59 , 60 , 114 , this paper reports the synthesis of novel periodic mesoporous organosilica by the reaction of amino group of (3-aminopropyl)triethoxysilane and toluene-2,4-diisocyanate, namely APS-TDU-PMO, with walls having urea bridges for Cu nanoparticles loading (Cu@APS-TDU-PMO, 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, attempts for the production of tetrazole derivatives through new methods have led to the use of 2-benzylidenemalononitrile and sodium azide along these lines 113 , 114 . In continuation of interest to develop new PMOs or their assemblies and exploring their catalytic activities 21 , 22 , 30 , 59 , 60 , 114 , this paper reports the synthesis of novel periodic mesoporous organosilica by the reaction of amino group of (3-aminopropyl)triethoxysilane and toluene-2,4-diisocyanate, namely APS-TDU-PMO, with walls having urea bridges for Cu nanoparticles loading (Cu@APS-TDU-PMO, 1 ). Furthermore, the Cu@APS-TDU-PMO was used as a highly efficient and recoverable nanoreactor for the synthesis of tetrazole derivatives 5 via three-component addition of aldehydes ( 2 ), malononitrile ( 3 ), and sodium azide ( 4 ) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The designed-procedures for the preparation of nanomaterials including magnetic nanoparticles and their catalytic activities are entirely verified in the field of greener and atom-economic reactions especially multicomponent reactions [4][5][6][7] . Indeed, the use of magnetic decorated organic structures is gaining significant attention in the field of catalysis for organic transformations, mainly due to opportunities in providing new structural diversities [8][9][10][11][12][13] . The design and construction of new structures is achieved with the aim of improving the structural characteristics and enhancing desired catalytic performance in the definite reactions.…”
mentioning
confidence: 99%